2018
DOI: 10.1038/s41598-018-25238-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for ATR/Rad3 in G1 phase

Abstract: Checkpoint kinases are important in cellular surveillance pathways that help cells to cope with DNA damage and protect their genomes. In cycling cells, DNA replication is one of the most sensitive processes and therefore all organisms carefully regulate replication initiation and progression. The checkpoint kinase ATR plays important roles both in response to DNA damage and replication stress, and ATR inhibitors are currently in clinical trials for cancer treatment. Therefore, it is important to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Interestingly, previous studies have suggested that blockage of elongating RNAPII is sufficient to induce ATR signaling in human cells (7), and ATR has been shown to be activated in G1-phase (46,47), when replication does not occur. We reasoned that signaling via phosphorylated RNAPII CTD might be a mechanism permitting ATR activation in G1.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, previous studies have suggested that blockage of elongating RNAPII is sufficient to induce ATR signaling in human cells (7), and ATR has been shown to be activated in G1-phase (46,47), when replication does not occur. We reasoned that signaling via phosphorylated RNAPII CTD might be a mechanism permitting ATR activation in G1.…”
Section: Resultsmentioning
confidence: 99%
“…40 ). Despite this well-established model, evidence for ATR activation in G1phase cells has been recently presented 41,42 . We report here that repression of Pol I transcription and nucleolar segregation are dependent on ATR activity throughout the cell cycle, even in G1 phase, when no sister chromatids are present, and resection of broken rDNA does not take place.…”
Section: Discussionmentioning
confidence: 99%
“…The dCK exists in phosphorylated form under basic conditions because it is constitutively active in cells responsible for the phosphorylation of Ser-74. ATR regulates dCK activity not only in cells with damaged DNA, but also in normal cells and in hematopoietic or epithelial cancer cells 28 . CLA significantly increased the level of ATR and ATM mRNA, which played an important role in dCK kinase phosphorylation 10 .…”
Section: Discussionmentioning
confidence: 99%